Ответы и объяснения

  • Участник Знаний
2013-05-11T09:05:07+00:00
Лучший Ответ!
2013-05-11T09:16:02+00:00

sinx+sin^2x/2=cos^2x/2  = 2sin(x/2)*cox(x/2) + sin^2(x/2)   - cos^2(x/2) = 0

  разделим на cos^2(x/2) получим

2tg(x/2)+ tg^2(x/2)   - 1 = 0

обозначим y=tg(x/2)

y^2 + 2y  - 1 = 0          D=B^2-4AC=2*2 -4*1*(-1) =  4 + 4 = 8 = (2*2^(0.5))^2

y1=(-B+D^(0.5))/2A = (-2 + 2*2^(0.5))/2 = -1 + 2^(0.5)

y2=(-B-D^(0.5))/2A = (-2 - 2*2^(0.5))/2 = -1 - 2^(0.5)

 

для y1  tg(x/2) =-1 + 2^(0.5)  ==>  x=2*arctg(-1 + 2^(0.5)) + pi*k  (k= ....,-2, -1, 0, 1, 2, ...)

для y2  tg(x/2) =-1 -  2^(0.5)  ==>  x=2*arctg(-1 - 2^(0.5)) + pi*k  (k= ....,-2, -1, 0, 1, 2, ...)